The Use of Ibuprofen Arginate in Pain Management Following Third Molar Surgery—A Scoping Review - Claudia Lorenzi; Ilaria Cammarota; Vincenzo Mazzetti; Claudio Arcuri; Paolo Carosi; Alberto Maria Pujia (Applied Sciences, 2025)
Background: The management of pain and inflammation after third molar extraction is essential for patient comfort and recovery. While conventional ibuprofen is widely used for pain relief, ibuprofen arginate, a formulation aimed at faster absorption, has shown potential for faster onset and enhanced efficacy. The aim of the present scoping review was to assess current evidence on the effectiveness of ibuprofen arginate in reducing pain and inflammation following third molar extraction compared to conventional ibuprofen. Methods: A comprehensive literature search was conducted in the MEDLINE database for studies published between 2002 and 2024, focusing on ibuprofen arginate’s impact on postoperative sequelae after third molar extractions. The studies included randomized controlled trials, cohort studies, and case–control studies in English. Results: Four studies, with a combined sample of 1245 patients, met the inclusion criteria. The findings suggest that ibuprofen arginate (200/400 mg) offers a faster onset of pain relief, with significant effects noticeable within 1–2 h. At six hours post administration, pain control was found to be similar between ibuprofen arginate and conventional ibuprofen. Additionally, a study found that ibuprofen arginate (600 mg) reduced postoperative swelling more effectively, although its impact on trismus was limited. Conclusions: Ibuprofen arginate seems to offer quicker pain relief and better control of swelling after third molar extractions compared to regular ibuprofen, making it a promising option for faster recovery. However, more studies are needed to fully understand its benefits and potential uses.